Burkina Faso : Priority Action Program to Implement the Poverty Reduction Strategy Paper 2004; 2006. (IMF Staff Country Reports; Country Report ;, 2005)
The Poverty Reduction Strategy Papers (PRSPs) on Burkina Faso focus on recapitulation of major long-term development. To improve the identification and targeting of the major public actions that contribute to combating poverty, the government has decided to prepare a Priority Action Program (PAP). It will also be necessary to enhance the dynamism of the National Statistical Coordination Council (CNCS) and to supplement the efforts of this organization by specialized commissions with a view to bringing together the major producers of statistical information.